Newly diagnosed type 2 diabetes may serve as a potential marker for pancreatic cancer. Issue 6 (17th June 2018) - Dankner, Rachel; Freedman, Laurence S.; Gerstein, Hertzel C.; Roth, Jesse; Keinan‐Boker, Lital
Abstract: Pancreatic cancer has an extremely highly case fatality. Diabetes is a well‐established strong risk factor for pancreatic cancer. Compared with a nondiabetic population, we previously reported a 15‐ and 14‐fold greater risk for detecting pancreatic cancer during the first year after diagnosing diabetes in adult women and men, respectively, which dropped during the second year to 5.4‐fold and 3.5‐fold, respectively, and stabilized around 3‐fold for the rest of the 11‐year follow‐up in our historical cohort. The population attributable risk during the 11‐year period was 13.3% and 14.1% in prevalent diabetic women and men, respectively. This means that one out of about every 8 patients diagnosed with pancreatic cancer has been previously diagnosed with diabetes. The globally high prevalence of diabetes and the aggravating implications of a delayed pancreatic cancer diagnosis call for newly‐onset diabetes to be considered a potential marker for an underlying pancreatic cancer and addressed accordingly.